2023
DOI: 10.3892/ijo.2023.5548
|View full text |Cite
|
Sign up to set email alerts
|

Role of gasdermin family proteins in cancers (Review)

Abstract: The gasdermin (GSDM) family comprises six proteins, including GSDMA-GSDME and Pejvakin. Most of these proteins have a crucial role in inducing pyroptosis; in particular, GSDMD and GSDME are the most extensively studied proteins as the executioners of the pyroptosis process. Pyroptosis is a highly pro-inflammatory form of programmed cell death and is closely associated with the incidence, development and prognosis of multiple cancer types. The present review focused on the current knowledge of the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…3D ). Subsequently, the pathway analysis further revealed potential downregulation of the PDGFRB pathway, involved in stromal cell activity and associated with improved patient response [ 49 ], while upregulation of pathways for antimicrobial peptides, FLT3 signaling, ephrin B reverse signaling and potential therapeutics for SARS ( Fig. 3E ), suggesting enhanced immune surveillance and interaction with tumor cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D ). Subsequently, the pathway analysis further revealed potential downregulation of the PDGFRB pathway, involved in stromal cell activity and associated with improved patient response [ 49 ], while upregulation of pathways for antimicrobial peptides, FLT3 signaling, ephrin B reverse signaling and potential therapeutics for SARS ( Fig. 3E ), suggesting enhanced immune surveillance and interaction with tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in the RCB-I (good response) components—RNA expression analysis revealed that lower expression of genes GPX1P1 and HBB are linked to less aggressive tumors [ 48 ], while those of thiosulfate sulfurtransferase (TST), NPIPA5 and GSDMB were overexpressed, linked to enhanced immune response and therapeutic effectiveness [ 49 , 50 ]. Mutational analysis showed positive association for therapeutic targets signatures TP53, MUC16 and RYR2 [ 51 , 52 ], but a negative in NEB, and CIN scores.…”
Section: Resultsmentioning
confidence: 99%